Don't take dandruff lightly! / Nurul Nadiah Saripshah - Saripshah, Nurul Nadiah (Faculty of Pharmacy, 2025)
Many people wish for beautiful hair and a healthy scalp. However, one of the main factors that hinders this goal from being achieved is dandruff. Dandruff may affect someone’s appearance and also lower their self-confidence.